Respuesta :
Answer:
C. (2, 1)
Step-by-step explanation:
-3y = x-5
x+ 5y = 7
Subtract x from both sides in the first equation. Write the second equation below it.
-x - 3y = -5
x + 5y = 7
Add the two equations above.
2y = 2
Divide both sides by 2.
y = 1
Substitute y with 1 in the second original equation and solve for x.
x + 5(1) = 7
x + 5 = 7
Subtract 5 from both sides.
x = 2
Answer: C. (2, 1)
Answer:
○ C. (2, 1)
Step-by-step explanation:
{-3y = x - 5 [Move -x to the left of the equivalence symbol]
{x + 5y = 7
{-x - 3y = -5
{x + 5y = 7
____________
2y = 2
__ _
2 2
y = 1 [Plug this back into both equations to get the x-coordinate of 2]; 2 = x
I am joyous to assist you anytime.